2015
DOI: 10.7307/ptt.v27i1.1522
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Research on Passenger Satisfaction With Public Transport Service in the City of Belgrade

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Traveling information is one of the key attributes on which the quality of a public transport service and customer satisfaction with such service is frequently measured. This finding is in accordance with the finding of Radnovic et al (2015) that visitors have a greater requirement for public transport information than local users when making public transport journeys to their destinations. Customer Services shared similarities with Fellesson and Friman (2008) of attitude and behavior of employees.…”
Section: Public Transport Service Dimensionssupporting
confidence: 92%
See 1 more Smart Citation
“…Traveling information is one of the key attributes on which the quality of a public transport service and customer satisfaction with such service is frequently measured. This finding is in accordance with the finding of Radnovic et al (2015) that visitors have a greater requirement for public transport information than local users when making public transport journeys to their destinations. Customer Services shared similarities with Fellesson and Friman (2008) of attitude and behavior of employees.…”
Section: Public Transport Service Dimensionssupporting
confidence: 92%
“…Generally, it was discovered that a greater number of passengers have assessed as displeased with the Malaysia mass transit. Radnovic et al (2015) conducted a research to determine the satisfaction of public transport users in Belgrade with the aim of improving their satisfaction. The results of the study showed a significant correlation between quality of service, attitude and behavior of employees, adequate information, quality of vehicles, line routes and timetable factors and passenger satisfaction with public transport services in Belgrade and that users are dissatisfied with the services provided by the operators.…”
Section: Customer Satisfaction With Public Transportmentioning
confidence: 99%
“…The increase in the quality of services can be considered as a very important element of pro-ecological strategy. The constant increase in the quality of services provided today is a necessity to increase interest in public transport, this thesis is confirmed by the results of research conducted by Dell'Olio et al, [24], Radnovića et al, [25] and Gajewską and Grigoroudis [26].…”
Section: Discussionsupporting
confidence: 72%
“…Formulated hypotheses are further examined based on P-value tests. P-value represents the minimum probability of error of first kind for which the established null hypothesis is still rejected (Radnović et al, 2015). According to P-value test, if the calculated P -value is smaller than 0.01, there is strong evidence against Ho.…”
Section: Methodsmentioning
confidence: 99%